La investigación urbana en México, 1980-1990 - Damián, Araceli (El Colegio de México A.C., 1991)
The purpose of this paper is to assess urban research in Mexico during the 1980s. The analysis conducted by the author is an uneven mosaic reflecting the state of knowledge in different disciplines that purport to deal with urban issues, as well as the main topics covered in such efforts. The study is divided into three sections: 1) continuing themes; 2) new themes on urban issues; 3) state policies regarding urban issues. The author notes that in the 1980s, research was conducted for the purpose of analyzing urban realities more explicitly, returning to themes discussed in the 1970s, but omitting the sweeping generalizations prevalent at the time and incorporating themes that had received little attention up until then, such as transportation, services, the environmental impact of economic development, and food and health problems. She also offers a description of studies that attempt to link state policies, the actors involved, and their impact (or lack of it) on urbanization processes, and discusses the regulatory functions carried out by the state.Such research not only dealt with old themes such as housing, urbanization, and social movements, but in addition, as of the 1970s, included criticism that enhanced their usefulness. During that decade, empirical research done on an individual or small- group basis -which limits the range and depth of the themes- was very common. Despite this, it has been possible to gain insights into specific situations concerning urban realities.